Aramid fiber composite insulation paper and preparation method thereof

Through boron nitride nanosheets, aramid nanofiber composite fiber felt and boron nitride nanosphere deposition technology, the problem of low thermal conductivity of aramid insulating paper is solved, and the high thermal conductivity and excellent insulation performance are achieved, and the equipment is improved Work efficiency and service life.

CN119121506APending Publication Date: 2024-12-13ELECTRIC POWER RES INST CHINA SOUTHERN POWER GRID CO LTD +1

Patent Information

Application Number
CN202411165311.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The low thermal conductivity of aramid insulating paper limits its application in electrical equipment, and existing thermal fillers damage electrical insulation while improving thermal conductivity.

Method used

A fiber felt composited with boron nitride nanosheets and aramid nanofibers is used, and a high-efficiency thermal conductivity network is constructed by depositing boron nitride nanospheres, and a chemical fluorination modification is used to enhance compatibility and reduce interface thermal resistance.

Benefits of technology

Aramid composite insulating paper is achieved to maintain excellent insulation performance while significantly improving thermal conductivity, improve in-plane and out-of-plane thermal conductivity, and extend the service life of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to the technical field of materials, in particular to aramid fiber composite insulation paper and a preparation method thereof. According to the preparation method provided by the invention, 2D boron nitride nanosheets and aramid nanofibers are spun into the fibrofelt, particularly 2D fluorinated boron nitride nanosheets (f-BNNS) and aramid nanofibers (ANF) are spun into the f-BNNS / ANF fibrofelt, so that an efficient oriented main heat-conducting network is constructed in the insulating paper, and the heat-conducting property of the insulating paper is improved; the 0D boron nitride nanospheres introduced by vacuum filtration are deposited in pores of the fibrofelt, so that the pores of a main heat-conducting network are filled, and an additional heat-conducting path is constructed. Compared with the existing composite insulation paper, the high-thermal-conductivity aramid fiber composite insulation paper obtained by the preparation method has the advantages that the in-plane thermal conductivity and the out-plane thermal conductivity are remarkably improved, and meanwhile, the high-thermal-conductivity aramid fiber composite insulation paper has good insulation performance and mechanical strength and has high thermal conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to aramid composite insulating paper and a preparation method thereof. Background Art

[0002] Polymer-based flexible insulating paper is widely used in important fields such as flexible electronics, electrical insulation, rail transit, etc. due to its outstanding advantages over metal or ceramic materials, as well as low cost, easy processing, excellent flexibility and light weight. Among them, aramid insulating paper has excellent electrical insulation performance, voltage breakdown resistance and good mechanical properties due to its stable chemical structure and has received widespread attention. However, the inherent low thermal conductivity of aramid insulating paper cannot promptly dissipate the high-density heat flow generated by the equipment, which greatly affects the working efficiency and service life of the equipment. Therefore, it is urgent to improve the thermal conductivity of aramid insulating paper.

[0003] The method of improving the thermal conductivity of insulating paper is usually through the addition of high-efficiency thermal conductive fillers. Carbon nanotubes, graphene, silver particles and nanowires are good thermal conductive fillers, which improve the thermal conductivity of insulating paper. However, its poor electrical insulation restricts its application in the electronics field. Another type of ceramic thermal conductive filler, such as alumina, silicon carbide, boron nitride, etc. Among various possibilities, 2D boron nitride nanosheets (BNNS) are one of the most effective ways to improve thermal conductivity due to their wide band gap and excellent two-dimensional phonon transport properties. However, due to the different composition and structure of BNNS and aramid, the interface defect problem seriously limits the further development of composite insulating paper.

[0004] In summary, in view of the problem that the thermal conductivity of aramid insulation paper is low and cannot meet the further development needs of current electrical equipment, it is urgent to develop a high thermal conductivity aramid insulation paper. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide an aramid composite insulating paper and a preparation method thereof. The aramid composite insulating paper provided by the present invention is an aramid composite insulating paper based on a fiber felt composite of boron nitride nanosheets (BNNS) and aramid nanofibers (ANF) and deposited with boron nitride nanospheres. The aramid composite insulating paper has excellent insulation properties and high thermal conductivity.

[0006] The present invention provides an aramid composite insulating paper, comprising: a fiber felt and boron nitride nanospheres deposited on the fiber felt; the mass ratio of the fiber felt to the boron nitride nanospheres is (6-9):(1-4); the fiber felt is composed of boron nitride nanosheets and aramid nanofibers in a mass ratio of (11-79):100.

[0007] The aramid composite insulating paper provided by the present invention comprises a fiber mat composed of boron nitride nanosheets and aramid nanofibers in a mass ratio of (11-79):100, also known as BNNS / ANF fiber mat; the mass ratio of the boron nitride nanosheets and the aramid nanofibers is (11-79):100, preferably (30-70):100. When the BNNS content is very low, it is difficult for BNNS to form an effective overlap as a thermal conductive filler, and when the BNNS content is too high, the porosity of the fiber will increase, limiting the improvement of thermal conductivity.

[0008] The particle size of the boron nitride nanosheets of the present invention is 100 nm to 300 nm, and the thickness of the boron nitride nanosheets is less than 2 nm; the diameter of the aramid nanofibers is 10 nm to 50 nm, and the length of the aramid nanofibers is greater than 3 μm. In certain embodiments of the present invention, the boron nitride nanosheets are preferably fluorinated hexagonal boron nitride nanosheets (f-BNNS), which are prepared from hexagonal boron nitride (h-BN) and a fluorinated coupling agent; the aramid nanofibers are para-aramid nanofibers; the fiber mat composed of the fluorinated boron nitride nanosheets and para-aramid nanofibers is also called f-BNNS / ANF fiber mat. The present invention uses the boron nitride nanosheet as a 2D boron nitride filler, especially a fluorinated boron nitride nanosheet as a 2D boron nitride filler. The conventional boron nitride nanosheet as a reinforcing filler can significantly improve the in-plane thermal conductivity of the composite paper due to the wide band gap and excellent two-dimensional phonon transport properties. However, the inherent composition and structural differences between the boron nitride nanosheet and the aramid nanofiber lead to very serious interface defects between the two. The chemical fluorination modification enhances the compatibility through chemical grafting. With the formation of interfacial hydrogen bonds, the interfacial interaction between the aramid nanofiber and the boron nitride nanosheet can be expected to be improved, and the interfacial thermal resistance can be significantly reduced. In addition, F, as the element with the strongest electronegativity, has extremely high electron adsorption force, and is expected to improve the electrical properties of the composite paper while modifying the interface between the filler and the matrix, and plays an important role in suppressing discharge.

[0009] The aramid composite insulating paper of the present invention further comprises boron nitride nanospheres deposited on the fiber felt; the mass ratio of the fiber felt to the boron nitride nanospheres is (6-9): (1-4). The present invention uses boron nitride nanospheres as 0D boron nitride fillers, and the particle size thereof is 100 nm-200 nm. If the size of the boron nitride nanospheres is too large, the structure of the BNNS / ANF fiber felt will be destroyed, and if the size of the boron nitride nanospheres is too small, the gaps between the BNNS / ANF fiber felts cannot be effectively filled. The boron nitride nanospheres form a compact and efficient additional heat-conducting network, making it easier for phonons to transfer between adjacent BNNS, so that the composite insulating paper maintains the in-plane thermal conductivity while significantly improving the out-of-plane thermal conductivity of the composite insulating paper.

[0010] The aramid composite insulating paper provided in the present application uses 0D boron nitride nanospheres and 2D boron nitride nanosheets as thermally conductive fillers. By spinning the 2D boron nitride nanosheets and aramid nanofibers into a composite fiber felt, the boron nitride nanosheets can be oriented in the aramid nanofiber matrix and a main thermal conductive network can be constructed, so that the obtained aramid composite insulating paper has high thermal conductivity while having excellent insulation properties.

[0011] The present invention also provides a method for preparing the aramid composite insulating paper described in any of the above technical solutions, comprising the following steps:

[0012] S1) mixing and spinning the aramid nanofiber fibril solution and the boron nitride nanosheets to obtain the fiber felt;

[0013] S2) depositing the boron nitride nanospheres on the fiber felt in step S1);

[0014] S3) hot-pressing the material obtained in step S2) at high temperature to obtain the aramid composite insulation paper.

[0015] The present invention firstly mixes the aramid nanofiber fibril solution and the boron nitride nanosheets to obtain the fiber mat; specifically, the present invention mixes the aramid nanofiber fibril solution and the boron nitride nanosheets, obtains a uniform spinning solution by ultrasonic treatment and magnetic stirring, then spins the prepared spinning solution, and dries the spinning material to obtain the f-BNNS / ANF fiber mat. In certain embodiments of the present invention, the mass ratio of the aramid nanofibers and the boron nitride nanosheets in the aramid nanofiber fibril solution is 100: (30~70). The present invention uses an electrostatic spinning process to spin ANF and BNNS into a BNNS / ANF fiber mat. BNNS has a large lateral size, especially f-BNNS has a large lateral size. The directional arrangement of f-BNNS is achieved through the spinning process, and a continuous heat conduction channel of f-BNNS along the axial direction of ANF is constructed, which greatly improves the in-plane thermal conductivity. Compared with single filler blends, the electrospun f-BNNS / ANF fiber mat has a larger specific surface area and porosity, which can significantly increase the contact area between the subsequent filler and the f-BNNS / ANF fiber mat, thereby enhancing the bonding force between the filler and the matrix.

[0016] In some embodiments of the present invention, the boron nitride nanosheets are fluorinated boron nitride. The fluorinated boron nitride of the present invention is obtained by mechanical exfoliation and fluorination of boron nitride, specifically, by grinding mechanical exfoliation of hexagonal boron nitride and fluorination modification of a fluorinated coupling agent. The present invention first mixes boron nitride, urea, ethanol and water to obtain a grinding suspension; the mass ratio of the boron nitride, urea, ethanol and water is 1: (25~35): (25~35): (5~15), preferably 1: (28~32): (28~32): (8~12), and more preferably 1: 30: 30: 10. After obtaining the grinding suspension, the grinding suspension is sequentially ground, centrifuged and dried to obtain boron nitride for mechanical glass; the grinding is carried out at a speed of 250~350 r / min, the grinding time is 64~80 h, and the grinding is preferably ball milling. After obtaining the boron nitride of mechanical glass, the mechanically stripped boron nitride, fluorinated coupling agent, ethanol and water are mixed, stirred, washed and dried to obtain fluorinated boron nitride; the mass ratio of the mechanically stripped boron nitride, fluorinated coupling agent, ethanol and water is 1: (15-25): (45-55): (5-15), preferably 1: (18-22): (48-52): (8-12); the mixing and stirring is carried out at a rotation speed of 1300-1700 r / min.

[0017] The aramid nanofiber fibril solution of the present invention uses aramid fiber as raw material, and is stripped by wet ball milling to obtain an aramid nanofiber fibril solution composed of aramid nanofibers. In certain embodiments of the present invention, the aramid nanofiber fibril solution is a para-aramid nanofiber fibril solution composed of para-aramid nanofibers. The aramid nanofiber fibril solution of the present invention is prepared by the following steps: washing the aramid fiber in an acetone solution, then mixing and stirring the washed aramid fiber, alkaline solution, DMSO and water, and then grinding the obtained material to obtain an aramid nanofiber fibril solution; the alkaline solution is selected from at least one of KOH or NaOH; the ratio of the washed aramid fiber, alkaline solution, DMSO and water is 1 g: (1~3) g: (400~600) mL: (8~12) mL; the grinding speed is 300~500 r / min, the grinding time is 40~80 min, and the grinding is preferably ball milling. The present invention uses the strong shear force and collision force of ball milling to split the macroscopic aramid fibers into aramid nanofibers, and introduces a certain amount of deionized water to assist the deprotonation reaction; the ball milling process can not only promote the penetration of the solution into the fiber, but also expand the contact area between the reactants, and at the same time refine the diameter of the aramid nanofibers. The presence of deionized water greatly accelerates the rate of the deprotonation reaction. In addition, the wet method strategy can minimize the mechanical damage to the aramid nanofiber structure caused by impact and collision, and ultimately achieve efficient and high-performance preparation of aramid nanofibers.

[0018] After obtaining the f-BNNS / ANF fiber mat, the present invention deposits the boron nitride nanospheres on the fiber mat. Specifically, the present invention uses the fiber mat as a filter membrane, and deposits the boron nitride nanosphere dispersion on the fiber mat by vacuum filtration; the boron nitride nanosphere dispersion is obtained by dispersing boron nitride nanospheres in isopropyl alcohol (IPA); the boron nitride nanospheres are the same as the above, and no further description is given. The present invention creatively directly uses BNNS / ANF fiber mat as a filter membrane, and uses vacuum filtration to deposit 0D boron nitride nanospheres on the BNNS / ANF fiber mat, which not only ensures the main lateral heat conduction network of the BNNS / ANF fiber mat, but also fills the pores between the BNNS / ANF fiber mats to form a compact and efficient additional heat conduction network, making it easier for phonons to transfer between adjacent BNNS. In addition, the BNNS / ANF fiber mat can also serve as a bridge between boron nitride nanospheres, while reducing the interfacial thermal resistance, providing more effective paths for phonon transmission, and ultimately achieving the improvement of the thermal conductivity of the insulating paper.

[0019] In certain embodiments of the present invention, the mass ratio of the fiber mat to the boron nitride nanospheres in the boron nitride nanosphere dispersion is (6-9): (1-4). Since boron nitride nanospheres are easy to aggregate and difficult to disperse, controlling the mass ratio of BNNS / ANF fiber mat to boron nitride nanospheres can not only fully fill the gaps between the BNNS / ANF fiber mats, but also effectively ensure molecular-scale mixing between the BNNS / ANF fiber mats and the boron nitride nanospheres.

[0020] After the boron nitride nanospheres are deposited on the fiber felt, the obtained material is hot-pressed at high temperature to obtain the aramid composite insulating paper. Specifically, the obtained material is hot-pressed at high temperature and vacuum-dried to obtain the aramid composite insulating paper. The temperature of the high-temperature hot pressing of the present invention is 120°C to 180°C, and the pressure of the high-temperature hot pressing is 7 MPa to 15 MPa. The vacuum drying time of the present invention is 10 to 15 h.

[0021] The present invention provides an aramid composite insulating paper and a preparation method thereof. The preparation method provided by the present invention is to construct a highly efficient and directional main thermal conductive network in the insulating paper by spinning 2D boron nitride nanosheets and aramid nanofibers into fiber felts, especially spinning 2D fluorinated boron nitride nanosheets (f-BNNS) and aramid nanofibers (ANF) into f-BNNS / ANF fiber felts, and introduce 0D boron nitride nanospheres by vacuum filtration and deposit them in the pores of the fiber felt, thereby filling the gaps in the main thermal conductive network and constructing an additional thermal conductive path. Compared with the existing composite insulating paper, the high thermal conductivity aramid composite insulating paper obtained by the preparation method of the present invention has significantly improved in-plane and out-of-plane thermal conductivity, and has both good insulation performance and mechanical strength, and has high thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is a scanning electron microscope image of para-aramid fiber;

[0023] Figure 2 is a scanning electron microscope image of h-BN;

[0024] Figure 3 Transmission electron microscopy image of f-BNNS;

[0025] Figure 4 is the transmission electron microscopy image of ANF;

[0026] Figure 5 is a scanning electron micrograph of f-BNNS / ANF fiber mat;

[0027] Figure 6 is a comparison diagram of the in-plane thermal conductivity of the composite insulating paper in Examples 1 to 8;

[0028] Figure 7 This is a comparison diagram of the through-surface thermal conductivity of the composite insulating paper in Examples 1 to 8;

[0029] Figure 8 This is a comparison diagram of the in-plane thermal conductivity of the composite insulating paper in Example 1 and Comparative Examples 1 to 8;

[0030] Fig. 9 This is a comparison chart of the volume resistivity of the composite insulating paper in Examples 1 to 8. DETAILED DESCRIPTION

[0031] The present invention discloses an aramid composite insulating paper and a method for preparing the same. A person skilled in the art may refer to the contents of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to a person skilled in the art and are considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0032] The present invention will be further described below in conjunction with embodiments:

[0033] Example 1

[0034] The present embodiment provides a high thermal conductivity aramid composite insulating paper based on f-BNNS / ANF fiber felt deposited with boron nitride nanospheres. The high thermal conductivity aramid composite insulating paper is prepared by spinning 2D fluorinated boron nitride nanosheets (f-BNNS) and aramid nanofibers (ANF) into fiber felts, and introducing 0D boron nitride nanospheres by vacuum filtration and depositing them on the f-BNNS / ANF fiber felt to obtain a more compact thermal conduction channel. In the present embodiment, the aramid nanofibers are para-aramid nanofibers obtained by wet ball milling, and have a diameter of 10 to 50 nm and a length greater than 3 μm; the f-BNNS are hexagonal boron nitride (h-BN) obtained by ball milling and modification with a fluorinated coupling agent, and have a particle size of 100 to 300 nm and a thickness of less than 2 nm; the particle size of the boron nitride nanospheres is 100 to 200 nm.

[0035] The method for preparing the high thermal conductivity aramid composite insulation based on f-BNNS / ANF fiber mat deposited with boron nitride nanospheres comprises the following steps:

[0036] Step 1) Using para-aramid fiber as raw material, stripping it into ANF fibril solution by wet ball milling, such as Figure 1 As shown, Figure 1 This is a scanning electron microscope image of para-aramid fiber:

[0037] Firstly, the para-aramid fiber was immersed in an acetone solution and cleaned by ultrasonic wave, and then dried in a vacuum oven for later use. Then, the washed and dried para-aramid fiber and potassium hydroxide (KOH) were added to a mixed solution of dimethyl sulfoxide (DMSO) and deionized water and magnetically stirred for 30 min at a speed of 800 r / min to obtain a uniform mixed solution. The ratio of para-aramid fiber, KOH, DMSO and deionized water was 1 g:1.5 g:500 mL:10 mL.

[0038] Step 2) h-BN is used as a raw material, and BNNS is obtained by ball milling and then collected by centrifugation. The obtained BNNS is further surface-modified with a fluorinated coupling agent to obtain f-BNNS, such as Figure 2 As shown, Figure 2 Scanning electron microscope image of h-BN:

[0039] First, h-BN was dispersed in a mixture of urea, anhydrous ethanol and deionized water to obtain a grinding suspension, wherein the ratio of h-BN, urea, anhydrous ethanol and deionized water was 1 g:30 g:30 g:10 g. Subsequently, the grinding suspension was placed in a ball mill and ground continuously for 72 h to obtain a mixed solution, and the ball mill speed was 300 r / min; then, the ground mixed solution was transferred to a centrifuge and repeatedly centrifuged in anhydrous ethanol at a high speed to collect the precipitate, and the centrifuge speed was 9000 r / min, and the centrifugation time was 15 min; then, the obtained precipitate was dried in a vacuum oven at 80 °C for 30 min to obtain mechanically exfoliated BNNS;

[0040] Further, the obtained BNNS is added to a mixed solution of a fluorinated coupling agent, anhydrous ethanol and deionized water and stirred rapidly to obtain a suspension, wherein the ratio of BNNS, fluorinated coupling agent, anhydrous ethanol and deionized water is 1 g: 20 g: 50 g: 10 g, and the mechanical stirring rate is 1500 r / min; finally, the obtained suspension is rinsed by centrifugation with anhydrous ethanol and deionized water, and f-BNNS is obtained after drying, such as Figure 3 As shown, Figure 3 Transmission electron microscopy image of f-BNNS.

[0041] Step 3) adding the f-BNNS to the ANF fibril solution to obtain a f-BNNS / ANF spinning solution, and electrospinning the spinning solution to obtain a f-BNNS / ANF fiber mat, such as Figure 4 As shown, Figure 4 Transmission electron microscope image of ANF:

[0042] First, the f-BNNS is added to the ANF fibril solution at a mass ratio of 30:100, and a uniform f-BNNS / ANF spinning solution is obtained by ultrasonic treatment and magnetic stirring. Then, the prepared spinning solution is transferred to a syringe, the needle height of the syringe is fixed and a voltage is applied to it, and the spinning solution is evenly sprayed on the surface of the collector to obtain f-BNNS / ANF fibers. Finally, the f-BNNS / ANF fibers collected after spraying are placed in a 60 ° C vacuum oven to remove moisture to obtain f-BNNS / ANF fiber felt; Figure 5 As shown, Figure 5 Scanning electron microscopy image of f-BNNS / ANF fiber mat.

[0043] Step 4) ultrasonically disperse the boron nitride nanospheres in isopropyl alcohol (IPA) with an ultrasonic power of 500 W, and use f-BNNS / ANF fiber felt as a filter membrane to deposit the boron nitride nanospheres on the surface of the f-BNNS / ANF fiber felt by vacuum filtration, wherein the mass ratio of f-BNNS / ANF fiber felt to boron nitride nanospheres is 9:1, thereby obtaining a high thermal conductivity aramid composite insulation paper based on boron nitride nanospheres deposited on f-BNNS / ANF fiber felt.

[0044] Step 5) The f-BNNS / ANF / boron nitride nanosphere composite insulation paper is hot-pressed at 10 MPa and 150° C. by a hot press, and dried at 60° C. in vacuum for 12 h to obtain a high thermal conductivity aramid composite insulation paper based on f-BNNS / ANF fiber felt deposited with boron nitride nanospheres.

[0045] Example 2

[0046] The difference between this embodiment and embodiment 1 is that in step 3), the mass ratio of the f-BNNS to the ANF fibril solution is 40:100.

[0047] Example 3

[0048] The difference between this embodiment and embodiment 1 is that in step 3), the mass ratio of the f-BNNS to the ANF fibril solution is 50:100.

[0049] Example 4

[0050] The difference between this embodiment and embodiment 1 is that in step 3), the mass ratio of the f-BNNS to the ANF fibril solution is 60:100.

[0051] Example 5

[0052] The difference between this embodiment and embodiment 1 is that in step 3), the mass ratio of the f-BNNS to the ANF fibril solution is 70:100.

[0053] Example 6

[0054] The difference between this embodiment and embodiment 1 is that in step 4), the mass ratio of the f-BNNS / ANF fiber felt to the boron nitride nanospheres is 8:2.

[0055] Example 7

[0056] The difference between this embodiment and embodiment 1 is that in step 4), the mass ratio of the f-BNNS / ANF fiber felt to the boron nitride nanospheres is 7:3.

[0057] Example 8

[0058] The difference between this embodiment and embodiment 1 is that in step 4), the mass ratio of the f-BNNS / ANF fiber felt to the boron nitride nanospheres is 6:4.

[0059] Comparative Example 1

[0060] ANF, f-BNNS and boron nitride nanospheres are ultrasonically mixed to obtain a mixed slurry, and ANF / f-BNNS / boron nitride nanosphere rough paper is obtained by vacuum filtration, and ANF / f-BNNS / boron nitride nanosphere insulating paper is obtained by high-temperature hot pressing.

[0061] Comparative Example 2

[0062] The difference between this comparative example and Example 1 is that BNNS is not fluorinated and is directly mixed with ANF for spinning, that is, in step 3), the mechanically stripped BNNS obtained in step 2) is directly added to the ANF fibril solution for mixed spinning.

[0063] Comparative Example 3

[0064] The difference between this comparative example and Example 1 is that h-BN is not stripped but directly mixed with ANF for spinning, that is, in step 3), h-BN is directly added to the ANF fibril solution for mixed spinning.

[0065] Comparative Example 4

[0066] The difference between this comparative example and Example 1 is that after obtaining the f-BNNS / ANF fiber mat in step 3), the obtained ANF / f-BNNS fiber mat is directly hot-pressed into paper at high temperature.

[0067] Comparative Example 5

[0068] The difference between this comparative example and Example 1 is that in step 4), the boron nitride nanospheres are replaced with boron nitride microspheres with a particle size of 50-100 μm.

[0069] Comparative Example 6

[0070] The difference between this comparative example and Example 1 is that in step 3), the mass ratio of the f-BNNS to the ANF fibril solution is 10:100.

[0071] Comparative Example 7

[0072] The difference between this comparative example and Example 1 is that in step 3), the mass ratio of the f-BNNS to the ANF fibril solution is 80:100.

[0073] Comparative Example 8

[0074] The difference between this comparative example and Example 1 is that in step 4), the mass ratio of the f-BNNS / ANF fiber felt to the boron nitride nanospheres is 4:6.

[0075] Examples 1 to 8 and comparative examples 1 to 8 were prepared according to the test standard, and thermal conductivity and volume resistivity of Examples 1 to 8 and comparative examples 1 to 8 were tested. The test results are as follows: Figure 6~Figure 9 As shown, Figure 6 is a comparison diagram of the in-plane thermal conductivity of the composite insulating paper in Examples 1 to 8, Figure 7 is a comparison chart of the through-surface thermal conductivity of the composite insulating paper in Examples 1 to 8, Figure 8 : is a comparison diagram of the in-plane thermal conductivity of the composite insulating paper in Example 1 and Comparative Examples 1 to 8, Fig. 9 This is a comparison chart of the volume resistivity of the composite insulating paper in Examples 1 to 8.

[0076] Figure 6 The corresponding data are shown in Table 1:

[0077] Table 1

[0078]

[0079] Figure 7 The corresponding data are shown in Table 2:

[0080] Table 2

[0081]

[0082] Figure 8 The corresponding data are shown in Table 3:

[0083] Table 3

[0084]

[0085] Fig. 9 The corresponding data are shown in Table 4:

[0086] Table 4

[0087]

[0088] according to Figure 6~Figure 9 From Tables 1 to 4, we can conclude that: 1. The in-plane thermal conductivity of the aramid composite insulation paper prepared by the present invention is greater than 15 W·m -1 K -1 (like Figure 7 As shown in the figure), it also has a high through-surface thermal conductivity (>0.15 W·m -1 K -1 ,like Figure 8 shown) and insulation properties (volume resistivity>10 15 Ω˙m, such as Fig. 9As shown). When the mass ratio of f-BNNS to ANF is within the range of the present invention, the in-plane thermal conductivity of the composite insulating paper increases first and then decreases with the increase of the f-BNNS ratio. When the mass ratio of f-BNNS to ANF is 60:100, the in-plane thermal conductivity of the composite insulating paper reaches a maximum value of 46.72 W·m -1 K -1 . This is because as the f-BNNS content increases, it gradually overlaps inside the fiber felt to form a through heat conduction path. When the f-BNNS content further increases to 70:100, the in-plane thermal conductivity begins to decrease because the excess f-BNNS will agglomerate to a certain extent, affecting the transmission of phonons. When the mass ratio of f-BNNS / ANF fiber felt to boron nitride nanospheres is within the range described in the present invention, the in-plane thermal conductivity of the composite insulating paper continues to increase, indicating that the establishment of additional heat conduction pathways still has a positive contribution to the through-plane thermal conductivity of the composite insulating paper.

[0090] 2. When the mass ratio of f-BNNS to ANF, f-BNNS / ANF fiber mat to boron nitride nanospheres is within the range of the present invention, the through-surface thermal conductivity of the composite insulating paper increases first and then decreases with the increase of the f-BNNS ratio, and increases with the increase of the mass ratio of f-BNNS / ANF fiber mat to boron nitride nanospheres. It can be seen that the establishment of an additional heat conduction path has a more positive effect on the through-surface thermal conductivity, reaching an exponential increase.

[0091] 3. When the composite insulating paper does not use the f-BNNS described in the present invention, but directly uses the peeled BNNS, or the unpeeled h-BN, due to the interface compatibility problem, its in-plane thermal conductivity is much lower than that of Example 1 described in the present invention.

[0092] 4. When boron nitride microspheres are used to replace boron nitride nanospheres, due to size mismatch, the micron-sized boron nitride spheres cannot be well filled in the gaps of f-BNNS / ANF fiber felt, so the in-plane thermal conductivity of the composite insulation paper is low.

[0093] 5. When the mass ratio of f-BNNS to ANF is lower or higher than the range described in the present invention, a lower mass ratio cannot form an effective overlap of the heat conduction path, while a higher mass ratio will form a large number of nanoparticle agglomerates, so the thermal conductivity of the composite insulating paper is limited.

[0094] 6. When the mass ratio of f-BNNS / ANF fiber felt to boron nitride nanospheres is lower than the range described in the present invention, due to the excessive content of boron nitride nanospheres, the agglomeration caused by excessive nanoparticles will lead to uneven filling of the pores, resulting in insufficient improvement in the thermal conductivity of the composite insulating paper.

[0095] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A kind of aramid composite insulating paper, characterized in that: include: A fiber felt and boron nitride nanospheres deposited on the fiber felt; the mass ratio of the fiber felt to the boron nitride nanospheres is (6-9):(1-4); The fiber felt is composed of boron nitride nanosheets and aramid nanofibers in a mass ratio of (11-79):

100.

2. The aramid composite insulating paper according to claim 1, characterized in that: The particle size of the boron nitride nanospheres is 100 nm to 200 nm.

3. The aramid composite insulating paper according to claim 1, characterized in that: The particle size of the boron nitride nanosheet is 100 nm to 300 nm, and the thickness of the boron nitride nanosheet is less than 2 nm.

4. The aramid composite insulating paper according to claim 1, characterized in that: The diameter of the aramid nanofiber is 10 nm to 50 nm, and the length of the aramid nanofiber is greater than 3 μm.

5. The aramid composite insulating paper according to claim 1, characterized in that: The fiber felt is made of boron nitride nanosheets and aramid nanofibers in a mass ratio of (30-70):

100.

6. The aramid composite insulating paper according to claim 1, characterized in that: The fluorinated boron nitride nanosheets are fluorinated hexagonal boron nitride nanosheets; The aramid nanofiber is a para-aramid nanofiber.

7. A method for preparing the aramid composite insulating paper according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1) mixing and spinning the aramid nanofiber fibril solution and the boron nitride nanosheets to obtain the fiber felt; S2) depositing the boron nitride nanospheres on the fiber felt in step S1); S3) hot-pressing the material obtained in step S2) at high temperature to obtain the aramid composite insulation paper.

8. The preparation method according to claim 7, characterized in that: In step S1), the boron nitride nanosheets are obtained by mechanically exfoliating and fluorinating boron nitride.

9. The preparation method according to claim 7, characterized in that: Step S2) specifically includes: using the fiber felt in step S1) as a filter membrane, and depositing the boron nitride nanosphere dispersion on the fiber felt by vacuum filtration.

10. The preparation method according to claim 7, characterized in that: In step S3), the temperature of the high temperature hot pressing is 120° C. to 180° C., and the pressure of the high temperature hot pressing is 7 MPa to 15 MPa.

Citation Information

Patent Citations

  • Polymer-based composite heat conduction material as well as preparation method and application thereof

    CN113912914A

  • Composite film with functions of insulation, heat conduction and electromagnetic shielding, preparation method and application

    CN117344549A

  • Insulating heat-conducting aramid paper and preparation method thereof

    CN117966511A

  • Heat-conducting and electric-insulating fiber for wearable treatment equipment and preparation process of heat-conducting and electric-insulating fiber

    CN118048709A

  • Composite paper structure containing aramid nanofiber and manufacturing method thereof

    JP2022114251A

Cited By

  • Method for preparing boron nitride self-supporting film through electrostatic spinning and film

    CN119753947A